Acupuncture for chronic diarrhea in adults: Protocol for a systematic review. Issue 4 (January 2017) - Qin, Zongshi; Li, Bo; Wu, Jiani; Tian, Jinhui; Xie, Shang; Mao, Zhi; Zhou, Jing; Kim, Tae-Hun; Liu, Zhishun
Abstract : Supplemental Digital Content is available in the text Abstract: Background: As 2 major common types of chronic diarrhea, functional diarrhea (FD) and diarrhea-predominant irritable bowel syndrome (IBS-D) affect 1.54% to 1.72% of people in China. Acupuncture is commonly used in clinical practice for patients with chronic diarrhea. Here, we present a protocol of systematic review aimed at systematically review all the clinical evidence on the effectiveness of acupuncture for treating FD and IBS-D in adults. Methods: The review will be performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement. We will search the following databases from their inception to January 2017: Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, China Biology Medicine disc, Wan-Fang Data, China National Knowledge Infrastructure, Citation Information by National Institute of Informatics, Oriental Medicine Advanced Searching Integrated System by Korea Institute of Oriental Medicine, and Japan Science and Technology Information Aggregator (J-stage). Clinical trial registrations will also be searched. Primary outcome measures are the change of bowel movements. The secondary outcomes include stool consistency, quality of life scales, other standardized rating scales, patient satisfaction, and acupuncture-related adverse effects assessment. Ethics and dissemination: This review does not require ethical approval and will be disseminated electronically or in print. PROSPERO registration number: CRD42015017574.